Konsentrasi Dan Lama Perendaman H2SO4 Terhadap Percepatan Perkecambahan Benih Kopi Arabika (Coffea Arabica L.) Var. S795 - Puspita, Yolanda Dewi; Erawati, Dyah Nuning (Agropross : National Conference Proceedings of Agriculture, 2019)
Var Arabica Coffee Seeds. S795 often experiences germination delays due to the hard condition of the seed coat so that water and air needed in the germination process cannot enter. Soaking H2SO4 solution is used to crack the hard seed coat and is impermeable to water and air, thus accelerating and increasing seed germination. The purpose of this activity is to determine the concentration and duration of soaking H2SO4 on the acceleration of Arabica coffee (Coffea arabica L.) Var seed germination. S795. Held in November 2018 until January 2019 at the State Polytechnic of Jember with an altitude of 89 masl. This activity uses a Completely Randomized Design (CRD) with the first treatment factor H2SO4 concentration (0%, 10%, 20%) and the second treatment factor H2SO4 soaking time (25 minutes and 30 minutes) and 4 replications. The results of this activity indicate that soaking H2SO4 concentration of 20% for 25 minutes accelerates the germination of Arabica coffee seeds (Coffea arabica L.) Var. S795 with a germination rate of 9.85% / day, germination capacity of 65% and a germination rate of 29 days.